Efisiensi Pemesanan Makanan dengan Aplikasi Android Berbasis Metode Rapid Application Development - Raden Bagus Bambang Sumantri; Fadli Anadrea; Lina Endarwati; Evan Irmansyah W. (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Technological advancements have provided efficient solutions for various activities, including those in the culinary business sector. With the growing use of smartphones, especially Android-based devices, there is a rising demand for a practical and fast food ordering system. This study aims to design and develop an Android-based food delivery application to address the limitations of manual ordering methods in restaurants, such as miscommunication and long queues. The development process adopts the Rapid Application Development (RAD) method, involving stages such as business modeling, data modeling, and application generation. Data were collected through observation, interviews, and literature review, and analyzed using qualitative methods. The implementation results show that the “PESANMAKAN” application improves the ordering process by providing complete menu information, order tracking, and transaction history features. Testing using the black-box method confirmed that all application functions operate as intended. In conclusion, this application effectively enhances restaurant operational efficiency and customer satisfaction, serving as a relevant digital solution for modern food ordering needs.